Nordic Europe after the Brexit vote: The five Nordic countries are reassessing their relations with the EU - Tobias Etzold; Christian Opitz (Stiftung Wissenschaft und Politik (SWP), 2016)
The UK's EU referendum is making waves in the Nordic countries. The vote could give a boost to Euro-critical parties across the region. However, it seems unlikely that EU members Denmark, Finland and Sweden will head for the exit in the foreseeable future or that non-members Norway and Iceland will loosen their ties with the EU to any significant extent. Nonetheless, with the UK's exit, the Nordic countries face the prospect of losing one of their key allies within the EU and will be compelled to rethink their positions in and towards the Union. There are already initial signs of adjustment - based on sometimes shared and sometimes divergent priorities. If the five countries are able to capitalise on their commonalities, Nordic cooperation in the context of an EU-27 may well gain traction. (SWP Comments)
Keywords: 320